Dental Transposition of Mandibular Canine and Lateral Incisor - Muhamad Abu-Hussein; Nezar Watted (Journal of Dental Problems and Solutions - Peertechz Publications, 2016)
Dental transposition is a form of ectopic eruption with change in position of normal adjacent teeth. Its prevalence is very low in general population and could be frequently missed on oral examination. This article reports a case of early orthodontic treatment of a rare unilateral mandibular right lateral incisor - canine transposition.